2019
DOI: 10.1177/0021998319846546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing conditions on solidification characteristics and mechanical properties of in situ magnesium metal matrix composites derived from polysilazane precursor

Abstract: Polymer-derived in situ magnesium metal matrix composites (P-MMMCs) were fabricated by injecting a liquid or cross-linked polysilazane precursor into molten magnesium by a stir-casting method at two different melt temperatures of 700 and 800℃. Microstructural analysis reveals that the composites fabricated at 700℃ exhibit uni-modal grain size distribution having more or less columnar-shaped grain morphology. On the contrary, bi-modal grain size distribution with predominantly dendritic grain morphology occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…found in-situ developed MMC at higher temperature showed brittle failure. 44 It is important to mention, cauliflower structures are not identified on the failed surface.…”
Section: Resultsmentioning
confidence: 99%
“…found in-situ developed MMC at higher temperature showed brittle failure. 44 It is important to mention, cauliflower structures are not identified on the failed surface.…”
Section: Resultsmentioning
confidence: 99%
“…Chelliah et al 21 investigated the effect of pyrolysis temperature on microstructural evolution of in-situ magnesium matrix composites containing SiCNO dispersoids. They found that the formation of brittle Mg 2 Si phase in molten magnesium can be minimized by decreasing the pyrolysis temperature from 800 to 700°C.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the formation of brittle Mg 2 Si phase in molten magnesium can be minimized by decreasing the pyrolysis temperature from 800 to 700°C. 21 It has been established that Mg is a good wettability agent to introduce ceramic particles into molten aluminum by stir-casting process. Although Mg helps in improving the wettability of molten aluminum, 22 the incorporation of Si-based polymer precursor into molten aluminum may form brittle Mg 2 Si phase which impairs the ductility of resulting composite.…”
Section: Introductionmentioning
confidence: 99%